Late Antiquity: The Regional Specific Nature of Intellectual Tradition - Litovchenko, Elena V.; Zaytseva, Irina V.; Rudneva, Maria A.; Zolotukhina, Natalia Ye.; Grechukhina, Anastasia A.; Dorokhov, Mihail I. (International Journal of Criminology and Sociology, 2022)
The primary purpose of the study is to investigate the specifics of the intellectual tradition prevailing in some regions of the Late Antique world. For the purpose of a comprehensive review of the problem, the authors focus on well-known intellectuals of the 5th–6th centuries, representing Gaul (Ausonius, Sidonius, Ennodius et al.), Alexandria (John Philoponus, Hypatia, Sinesius of Cyrene et al.), Africa (Fulgentius, Priscian, Corippus), Isauria (Candidus Isaurus). Despite the fact that, under the influence of objective factors (Christianization, barbarians), the intellectual tradition changed from its ancient model to the medieval one, it fulfilled its most important task - to preserve the best from the treasury of ancient thought and adapt the ancient heritage to a changing world. In conclusion, the outcomes of the study demonstrate various examples of intellectual tradition and the fortunes of “people of written culture” (literati).